Increased risk of hospital admission for ICD‐9‐CM psychotic episodes following admission for epilepsy. (4th July 2018) - Rossi, Kyle C.; Kim, Anna M.; Jetté, Nathalie; Yoo, Ji Yeoun; Hung, Kenneth; Dhamoon, Mandip S.
Summary: Objective: To determine whether epilepsy admissions are associated with a higher readmission risk for psychotic episodes compared to admissions for other medical causes. Methods: The Nationwide Readmissions Database is a nationally representative dataset from 2013. We used International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM) codes to identify medical conditions. There were 58 278 index admissions for epilepsy, and this group was compared against admissions for stroke (n   =   215 821) and common medical causes (pneumonia, urinary tract infection [UTI], congestive heart failure [CHF], and chronic obstructive pulmonary disease [COPD], n   =   973 078). Readmission rates for psychotic episodes within 90 days from discharge for index hospitalizations were calculated. Cox regression was used to test for associations between admission type and readmission for psychotic episodes up to 1 year after index admission, in univariate models and adjusted for multiple medical, social, and psychiatric variables. Results: Up to 90 days from index admission, there were 683/100 000 readmissions for psychotic episodes in the epilepsy group, 92/100 000 in the stroke group, and 58‐206/100 000 in the medical group. The relative rate of readmission in the epilepsy group was highest in the first 30 days following index admission (311/100 000). Unadjusted hazard ratio (HR) for readmission for psychotic episodes within 1 year in the epilepsy group compared to the stroke group was 6.58 (95% confidence interval [CI] 5.69‐7.61, P  <   2 × 10 −16 ), and 4.41 compared to the medical group (95% CI 4.00‐4.85, P  <   2 × 10 −16 ). The fully adjusted HR for readmission in the epilepsy group remained elevated at 3.63 compared to the stroke group (95% CI 3.08‐4.28, P  <   2 × 10 −16 ), and 1.95 compared to the medical group (95% CI 1.76‐2.15, P  <   2 × 10 −16 ). Confounding factors most strongly associated with psychosis readmission were documented psychosis history at the time of index admission, younger age, and lower income quartile. Significance: An epilepsy admission was independently associated with subsequent hospital readmission for psychotic episodes, even after adjustment for confounding variables.